Exploring Simulation and Debriefing as an Educational Strategy for Perioperative Nurse Learners: A Case Study - Clendinneng, Debra B (University of Ottawa (Canada), 2011)
Simulation and debriefing are indivisible components of an important educational strategy being used for educating healthcare professionals. Simulation provides reproducible experiences so learners acquire essential cognitive and psychomotor skills through repetitive practice in environments that mimic clinical reality but eliminate patient risk. Postsimulation debriefing, the cornerstone of this experiential process, is a structured, guided activity where learners are encouraged to collectively and individually explore and reflect upon their experiences in order to improve future performances. The aim of this qualitative case study was to explore simulation and debriefing as experienced by a purposive sample of nine nurse learners and one facilitator while participating in a post-graduate, perioperative nursing program. Guiding questions were: 1. What are the perceptions of perioperative nurse learners participating in the simulation and debriefing process? 2. How does post-simulation debriefing impact the learning process for nurses participating in a perioperative clinical laboratory course? 3. How does the facilitator experience and explain debriefing within this case study? Through researcher observation, video capture of multiple simulations and postsimulation debriefings, semi-structured interviews and learner journaling, common themes emerged that relate to benefits and drawbacks to learning in the simulation environment. The study's findings are reported within participant profiles. Recommendations are made regarding the design of simulation experiences, the use of a debriefing conceptual framework to enhance experiential learning, and ways to enhance debriefer efficacy. Implications of the study revolve around the complexity of designing and enacting simulation and postsimulation debriefing that provides all learners with a positive experiential learning opportunity. When optimal conditions exist, simulation and debriefing can result in transformative learning that is transferrable from the simulation laboratory to the clinical setting. Areas for future research include investigating what types of simulation and debriefing experiences help learners to transition knowledge, skills and judgment from the simulation setting to the clinical environment. Researchers must also determine if simulated experiences can be considered equivalent to direct patient care and thus be used confidently in this manner for educating healthcare professionals.
Keywords: Education, Health.